Isolation and Characterization of Colistin-Resistant Enterobacteriaceae from Foods in Two Italian Regions in the South of Italy - Rosa Fraccalvieri; Angelica Bianco; Laura Maria Difato; Loredana Capozzi; Laura Del Sambro; Stefano Castellana; Adelia Donatiello; Luigina Serrecchia; Lorenzo Pace; Donatella Farina; Domenico Galante; Marta Caruso; et al. (Microorganisms)
The emergence of colistin-resistant Enterobacteriaceae in food products is a growing concern due to the potential transfer of resistance to human pathogens. This study aimed to assess the prevalence of colistin-resistant Enterobacteriaceae in raw and ready-to-eat food samples collected from two regions of Italy (Apulia and Basilicata) and to evaluate their resistance phenotypes and genetic characteristics. A total of 1000 food samples were screened, with a prevalence of 4.4% of colistin-resistant Enterobacteriaceae. The majority of the isolates belonged to Enterobacter spp. (60%), followed by Moellerella wisconsensis, Atlantibacter hermannii, Klebsiella pneumoniae, and Escherichia coli, among others. Genomic sequencing and antimicrobial susceptibility testing revealed high levels of resistance to β-lactams, with most isolates exhibiting multidrug resistance (MDR). Notably, seven isolates harbored mcr genes (mcr-1, mcr-9, and mcr-10). Additionally, in four of them were predicted the IncHI2 plasmids, known to facilitate the spread of colistin resistance. Furthermore, 56 antimicrobial resistance genes were identified, suggesting the genetic mechanisms underlying resistance to several antibiotic classes. Virulence gene analysis showed that E. coli and other isolates carried genes linked to pathogenicity, increasing the potential risk to public health. This study emphasizes the role of food as a potential reservoir for colistin-resistant bacteria and the importance of monitoring the spread of AMR genes in foodborne pathogens.